PENGEMBANGAN PERANGKAT PEMBELAJARAN BERBASIS MODEL PROBLEM SOLVING UNTUK MENINGKATKAN KEMAMPUAN KOGNITIF PADA MATERI GELOMBANG BUNYI SISWA KELAS VIII SMP - Hamdani, Riza Nugra; Syahril, Syahril; Zulhelmi, Zulhelmi (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: The learning device developed is a problem solving model based on soundwave material for grade VIII SMP students, consisting of a Learning Implementation Plan(RPP), Student Worksheets (LKPD), and Learning Outcomes Test. The purpose of thisstudy was to determine the validity of learning tools based on problem solving models onsound wave materials. This type of research is a Research and Development (R&D) with a4D model design. The research instrument used was the RPP validation assessment sheet,LKPD, and the Learning Outcomes Test which were used by the validator to assesslearning tools. Data analysis in this study used descriptive analysis. Based on the resultsof the validity data analysis, the average value of the validity of the lesson plan was 3.60with a very high category, the average validity of LKPD was 3.49 with a very highcategory and the Learning Outcomes Test was 3.38 with a very high category, so that theaverage -The overall average of learning devices is 3.49 with a very high category. Thus,learning tools based on the problem solving model are declared valid and suitable for usein sound wave material in class VIII SMP.Key Words: Physics Learning Tools, Models, Problem Solving, Cognitive Ability